Designing Training Program to Solve Competencies Gap in Non-Managerial Level, Low Management Level, and Middle Management Level at PT Frolant - Maharani Gitaastuti; Nur Arief Rahmatsyah Putranto (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2021)
Competencies gap is now becoming a common problem in Indonesia. Research done by the World Bank in 2019 shows that one of the reasons for the competencies gap is limited opportunities for on-the-job training, only 5% of the workforce reported receiving formal training. One of the companies in Indonesia that experiences a problem of competencies gap is PT Frolant. PT Frolant is a manufacturer of instant food and drinks in Indonesia. The problem of competencies gap is shown from the low internal readiness of the company, employees don’t have the competencies required by the company, especially competencies for higher positions of Supervisor and Manager. The proposed solution to solve the competencies gap problem in PT Frolant is by designing new training programs. The process of designing a new training program included conducting training need analysis, design training based on competency, and using the Kirkpatrick Model to evaluate the training program. The research findings show that the company needs to do several improvements in order to create a training program that can solve the problem of the competencies gap. Those including aligning competency standards with organizational goals and organizational design; use several tools to be better in identifying employees with competency gap; differentiate between soft skill and hard skill or between strategic knowledge and operational knowledge in designing training; and perform all four steps of Kirkpatrick Model in evaluating training. Designing training programs based on competencies aims to help PT Frolant improving employee performance that will further improve company performance.